Education as a component of law enforcement professionalism: the concept and its measurement - Adams, Reed (American journal of criminal justice, 1981)
The. lack of empirical studies of education as a structural variable. within theoretical modelt, of professionalization was disucssed. Also, a scale. designed to measure. education, as a camponent of the. concept of low enforcement as a. profoession was developed. lnterpreted as valid and reliable, the scale. was employed in a survey of North Carolina law enforcement personnel. Although it was concluded that many law enforcement personnel did not identify education as an element of the concept of law enforcement as a profassion, a minority strongly endorsed education. Law enforcement. personnekl overwhelmingly phefered criminal justice. curricula over those. of other disciplines, and many anticipated participation in criminal justice educational programs. It was concluded the conceptualization of education as, a component of law enforcement as a profession was, emerging. However, such conceptualieation was not felt to be pervasive within the law enforcement community.